2012
DOI: 10.1002/ijc.27964
|View full text |Cite
|
Sign up to set email alerts
|

RUNX family: Regulation and diversification of roles through interacting proteins

Abstract: The Runt-related transcription factors (RUNX) belong to an ancient family of metazoan genes involved in developmental processes. Through multiple protein-interacting partners, RUNX proteins have been implicated in diverse signaling pathways and cellular processes. The frequent inactivation of RUNX genes in cancer indicates crucial roles for RUNX in tumor suppression. This review discusses the abilities of RUNX proteins, in particular RUNX3, to integrate oncogenic signals or environmental cues and to initiate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
164
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(168 citation statements)
references
References 161 publications
(194 reference statements)
4
164
0
Order By: Relevance
“…Recently, Bresciani and colleagues reported that RUNX1 can drive the emergence of nascent hematopoietic stem cells without its heterodimeric partner CBFb (24), suggesting parts of RUNX1's biologic functions are independent of CBFb. In addition, lots of cellular proteins, Myb, Ets, ALY, TLE/Groucho, p300, CBP, YAP, SIN3A, MOZ, PML, PRMT1, TAL1, MLL, Shp2, SWI/SNF, etc., have been described to interact with RUNX1 (25). Of note, RUNX1 interacted with several transcriptional factors through a dynamic combinatorial mechanism to orchestrate hematopoietic differentiation (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Bresciani and colleagues reported that RUNX1 can drive the emergence of nascent hematopoietic stem cells without its heterodimeric partner CBFb (24), suggesting parts of RUNX1's biologic functions are independent of CBFb. In addition, lots of cellular proteins, Myb, Ets, ALY, TLE/Groucho, p300, CBP, YAP, SIN3A, MOZ, PML, PRMT1, TAL1, MLL, Shp2, SWI/SNF, etc., have been described to interact with RUNX1 (25). Of note, RUNX1 interacted with several transcriptional factors through a dynamic combinatorial mechanism to orchestrate hematopoietic differentiation (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…It lacks several well-recognized regulatory domains in the C terminus. 18,38 These facts prompted us to do a cross-species comparison to examine evolutionary conservation of this isoform. We found that the homologous mouse sequence of human exon 7A lacked sequences relating to splice acceptor AG and stop codon TAA, indicating that there is no ortholog of human RUNX1a in mice ( Figure 1A-B).…”
Section: Mice Lack Runx1a Orthologmentioning
confidence: 99%
“…In earlier studies, it has been shown that RUNX2 binds and recruits CEBPd to promoter enabling transcription and precluding the requirement for direct DNA binding (46). Alternatively, since RUNX3 is known to establish multiple protein-interacting partners, it is possible that RUNX3 might control HMOX1 transcription indirectly through interaction with transcription factors known to regulate HMOX1 levels (47).…”
Section: Discussionmentioning
confidence: 99%